Por um ensino de história antirracista: possibilidades e perspectivas a partir do livro didático do ensino fundamental II - Esteves, Anderson Luiz Marques (2022)
In this work we seek to discuss teaching of History from na anti-racist perspective, for which we will use the textbook as a research object. The debate on racial issues is a recurring theme in school Spaces, yet the theoretical and pedagogical bases offerd to teachers and students lack current concepts about racismo. In this sense, we seek to investigate how the textbook reproduces stereotypes presente in Society about Africa, black people, African and Afro Btazilian culture, through images, texts and activities. Against these questions, we propose to discuss some concepts in the form of entries that represent na anti-racist attitude in teaching, in the face of the entire process of marginalizations and exclusion of black people throughout history. With that, the product elaborated at the end of this work, is a samll insert of a textbook, with concepts related to racial themes and na anti-racist teaching posture.